2005
DOI: 10.1007/s00467-005-2051-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stimulants on 24-h ambulatory blood pressure in children with ADHD: a double-blind, randomized, cross-over trial

Abstract: Millions of children with attention deficit hyperactivity disorder (ADHD) are treated with stimulant medications. To evaluate cardiovascular risk, 24-h ambulatory blood pressure monitoring (ABPM) was performed on and off medication. Thirteen subjects underwent APBM both on stimulant therapy and placebo using a placebo-controlled, double-blind, randomized, cross-over design. After a 3-day run-in followed by a 24-h monitoring period, subjects crossed over to the alternate therapy for repeated ABPM. Subjects demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 18 publications
(22 reference statements)
3
80
1
1
Order By: Relevance
“…Compared with the study by Winterstein et al, the observation period of our study was much longer (9.5 vs. 2.3 years) and this may explain the difference in estimated risk. Furthermore, our prospective follow-up may also offer less biased results than the previous retrospective studies in children and adolescents (Winterstein et al 2007(Winterstein et al , 2009Cooper et al 2011;Schelleman et al 2011;Olfson et al 2012) and in adults (Holick et al 2009;Habel et al 2011;Schelleman et al 2012). Only two of the previous studies included patients with ADHD and estimated the effect of treatment (Winterstein et al 2007;Olfson et al 2012), whereas the rest of the previous studies compared users to non-users, essentially comparing patients with ADHD to normal controls without ADHD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Compared with the study by Winterstein et al, the observation period of our study was much longer (9.5 vs. 2.3 years) and this may explain the difference in estimated risk. Furthermore, our prospective follow-up may also offer less biased results than the previous retrospective studies in children and adolescents (Winterstein et al 2007(Winterstein et al , 2009Cooper et al 2011;Schelleman et al 2011;Olfson et al 2012) and in adults (Holick et al 2009;Habel et al 2011;Schelleman et al 2012). Only two of the previous studies included patients with ADHD and estimated the effect of treatment (Winterstein et al 2007;Olfson et al 2012), whereas the rest of the previous studies compared users to non-users, essentially comparing patients with ADHD to normal controls without ADHD.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, when these analyses were performed using the stimulant dosage at the time of the cardiovascular event, we found a significant inverse dose-response relationship. Only one previous study has examined a dose-response relationship, and found current treatment with methylphenidate to be associated with an increased risk of serious cardiovascular events and death in adults with ADHD, with an HR for all causes of death of 1.74 (1.60-1.89) compared with non-users (Schelleman et al 2012). Similar to our findings, the study found that the risk was inversely related with current dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have demonstrated statistically significant increases in heart rate and blood pressure (BP) with stimulants (Samuels et al 2006;Stiefel and Besag 2010;Hammerness et al 2011), including studies showing increases from 3 to 10 beats per minute (bpm), 1-8 millimeters of mercury (mmHg), and 1-15 mmHg for heart rate, systolic BP, and diastolic BP, respectively. The longterm effects of stimulant medication on CV health have not been fully described, although one study suggests that increases in heart rate and BP persist over time (Hammerness et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several studies about the cardiovascular safety of stimulant medications were carried out. [7][8][9][10][11][12] Stimulants and MPH increase blood pressure (BP) and heart rate (HR) in patients with ADHD, [13][14][15][16][17] although these cardiovascular effects do not seem to be severe. [18][19][20] Nevertheless, most evidence is based on clinical reports from small populations, so it remains controversial whether the use of stimulants is potentially associated with serious adverse cardiovascular events or otherwise.…”
Section: Introductionmentioning
confidence: 99%